FACTORS INFLUENCING PERFORMANCE OF MICRO, SMALL AND MEDIUM ENTERPRISE PROJECTS IN NAIROBI CITY COUNTY, KENYA. (A CASE OF KENYA INDUSTRIAL ESTATES LIMITED) - Zighe Wawasi, Vivian Salome; Were, Dr. Susan (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of this study was to find out factors influencing the performance of Kenya Industrial Estates Limited Micro, Small and Medium Enterprises (MSME's) projects in Nairobi City County, Kenya. The objectives of the study were to determine the extent to which the project scope, project team's competency, project implementation and project funding influence implementation of projects in Kenya Industrial Estates Limited, Nairobi City County, Kenya. Materials and Methods: The target population of the study was 157 respondents comprising of 7 top managers, 50 middle level managers and 100 operational staff at Kenya Industrial Estates Limited. The main data collection instrument for this study was questionnaires for all the respondents. The findings of this study was summarized and presented using descriptive analysis methods. Content analysis will be used for qualitative data. Results: Finding of the study indicated that 33% of the respondent showed that project monitoring on monthly basis had the highest score, quarterly monitoring scored 26%, annual at 14%, weekly at 10% and last daily at 6%. From the study findings, all the respondents (100%) agreed that all projects are sufficiently funded by KIE for MSMEs. The study also concludes that stakeholder's involvement affected project success, whereas project scoping is a key factor in determining the performance of any project. The study established that most of the respondents were satisfied with the team's capacity as factor affecting project performance achieving its goals and objectives. Recommendations: The study recommends that in order to achieve completion of projects, proper project funding is crucial and all activities to ensure there is adequate funding need to be put in place. Finally KIE should ensure that there is adequate early planning for project M&E activities (including the human and financial resources) and involvement of all stakeholders in development and implementation of the MSMEs projects.